2019
DOI: 10.1002/bies.201900128
|View full text |Cite
|
Sign up to set email alerts
|

Close Encounters of the Viral Kind: Cross‐Kingdom Synergies at the Host–Pathogen Interface

Abstract: The synergies between viral and bacterial infections are well established. Most studies have been focused on the indirect mechanisms underlying this phenomenon, including immune modulation and alterations to the mucosal structures that promote pathogen outgrowth. A growing body of evidence implicates direct binding of virus to bacterial surfaces being an additional mechanism of synergy at the host-pathogen interface. These cross-kingdom interactions enhance bacterial and viral adhesion and can alter tissue tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Recent studies have revealed that the high mortality caused by the Spanish influenza was due to bacterial pneumonia combined with influenza or bacterial pneumonia following influenza 2–5 . The viral–bacterial complexes play unique roles in pathogenesis and can alter virulence potential 6 . IAV infection has been shown to enhance susceptibility to a secondary bacterial infection 2,4,5,7–10 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have revealed that the high mortality caused by the Spanish influenza was due to bacterial pneumonia combined with influenza or bacterial pneumonia following influenza 2–5 . The viral–bacterial complexes play unique roles in pathogenesis and can alter virulence potential 6 . IAV infection has been shown to enhance susceptibility to a secondary bacterial infection 2,4,5,7–10 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of excellent reviews regarding S. pneumoniae secondary infection following influenza have been presented 4–6,9,13–15 . However, other streptococci including pathogenic Streptococcus pyogenes (group A streptococcus ) and commensal streptococci (oral mitis group streptococci) also colonize in the upper respiratory tract in various ways (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations